Asymptomatic Clostridium difficile carriage rate post-fecal microbiota transplant is low: a prospective clinical and stool assessment. (July 2018) - Allegretti, J.R.; Allegretti, A.S.; Phelps, E.; Xu, H.; Kassam, Z.; Fischer, M.
Abstract: Objectives: We aimed to assess the asymptomatic Clostridium difficile carriage rates following fecal microbiota transplantation (FMT). Methods: All patients who underwent FMT for recurrent Clostridium difficile infection (CDI) via colonoscopy or sigmoidoscopy between June 2013 and April 2015 and had a minimum of 8-week follow-up post FMT at two tertiary care referral centres were included in the study. Patients were prospectively followed both clinically and with stool assessments for 8 weeks post FMT. Assessments occurred at 1 week and 4 weeks post FMT to assess for failure. Failure was defined as presence of diarrhoeal symptoms and a positive CDI stool test by polymerase chain reaction for toxin gene (PCR) at any time point during the 8-week follow-up period. CDI stool testing using PCR was performed at weeks 1 and 4 post FMT in asymptomatic patients as well. Results: 167 patients were included. Twenty-eight patients (16.7% (28/167)) were FMT failures throughout the 8-week period. At week 1, seven patients had already failed the FMT. Of the remaining 160 patients, 144 were asymptomatic, and among these, 141 were negative for C. difficile toxin gene by PCR. This resulted in an asymptomatic carriage rate of 2.1% (3/144). At week 4, 143 patients had not yet failed FMT. Of these patients 129 patients were asymptomatic and among those, 125 were negative by PCR, resulting in an asymptomatic carriage rate of 3% (3/129). Conclusions: Asymptomatic carriage after FMT is rare. This suggests that testing for cure after FMT in asymptomatic patients is not necessary.